A Complementary Feeding Intervention for Fathers and Mothers in Northern Nigeria Improves Children's Minimum Meal Frequency and Consumption of Eggs and Fish. (7th June 2021) - Flax, Valerie; Ipadeola, Abiodun; Schnefke, Courtney; Kwasu, Sarah; Mikail, Abdulrahaman; Bose, Sujata; Brower, Alice; Edwards, Susan
Abstract: Objectives: The objective of this study was to measure the effects of a social behavior change communication (SBCC) intervention on fathers' and mothers' complementary feeding knowledge and attitudes, fathers' support for complementary feeding, and children's dietary diversity and meal frequency. Methods: This study used cross-sectional surveys of cohabiting fathers and mothers with a child 6–23 months before (N = 497) and after (N = 495) the intervention in Igabi local government area, Kaduna State, Nigeria. Participants were randomly sampled within 99 clusters selected proportional to population size. Regression models weighted for the survey design, including inverse propensity weights to adjust for differences in sociodemographic characteristics of the cross-sections, were used to assess before/after differences. Alive & Thrive's 12-month intervention engaged fathers through community meetings, religious services, and mobile phone text and voice messages. Mothers received home visits from community health extension workers (CHEWs), which fathers also could attend. SBCC materials included TV and radio messages, sermon guides, counseling cards, pamphlets, posters, and feeding bowls. Results: Exposure of fathers to CHEW visits, fathers and mothers to mass media messages, and fathers to text/voice messages increased from baseline to endline. Fathers' and mothers' knowledge of the timing of introduction of different foods and meal frequency shifted toward the global recommendations. Fathers' support for child feeding by providing money for food increased (79% to 90%, P < 0.001). The percentage of children with minimum dietary diversity did not change (62% to 65%, P = 0.358). The percentage of children who consumed fish (36% to 44%, P = 0.012) and eggs (8% to 20%, P = 0.004), had minimum meal frequency (58% to 73%, P < 0.001), and had minimum acceptable diet (40% to 52%, P < 0.001) increased from baseline to endline. Conclusions: A multipronged SBCC intervention improved fathers' and mothers' knowledge of complementary feeding, increased fathers' support for complementary feeding, and modified some complementary feeding practices. Funding Sources: This research was funded by the Alive & Thrive initiative, managed by FHI Solutions, and currently funded by the Bill & Melinda Gates Foundation, Irish Aid, the Tanoto Foundation, UNICEF, and the World Bank.